Design By Scenarios, Improving The Creative Thinking For Product Design (2005)
The Design Department at Icesi University has made its own proposal for the use of forecasting scenarios in the design process and has been testing it for five years, developing design projects which subjects are closely related to the social circumstances of Colombia. During these years interesting pedagogic and design results have arisen. The method of design by scenarios is a creative vision tool that helps designers in the concept creation of future products. This tool moulds feasible future situations, using the analysis of the dynamics of the present time as a starting point. This tool has proved to be very useful in the reduction of uncertainty of decision making processes, that design directors must face when they must achieve design results for terms longer than ten years. Design by scenarios is an inductive method of group work, based on the consideration of several questions related to several issues it must meet, such as political, economical, social, technological, environmental and cultural. The analysis and debate of these questions results in the identification of a list of present time’s forces surely will influence this activity in the future. The interaction of these forces enables to construct several feasible scenarios that could take place in ten years time, to define different products and services. Our design departmen